Comparative analysis of load responses and deformation for crust composite foundation and pile-supported embankment - Wang, Ying; Chen, Yonghui; Hu, Zhenhua; Feng, Qiang; Kong, Desen (Penerbit Universiti Kebangsaan Malaysia, 2017)
Ground improvement using artificial crust composite foundation, consisting of stabilization of soft clay and composite foundation, is an effective technique for the treatment of deep soft soil layers under infrastructure embankments. In this study, the load responses and settlement performance of this improvement technique were investigated using two centrifuge model tests to compare the variations of the vertical deformation, pore water pressure, axial force of the piles and tensile stress at the bottom of the artificial crust in the crust composite foundation with those in pile-supported embankment. The results of centrifuge model tests showed that the load responses and settlement performance of artificial crust composite foundation was different from the pile-supported embankment, which displayed mainly that the final middle settlement of crust composite foundation can be reduced by about 15% compared with those of pile-supported embankment with the same length of pile and construction cost. The deformation of the crust with the characteristics of the plate was found based on the change of the tensile stress. Additionally, the excess pore water pressure in the crust composite foundation was lower owing to the stress diffusion effect of the crust during the loading period and the dissipation rate of excess pore water pressure was slower due to lower permeability of the crust at the same loading period. Eventually, the axial force of the middle piles was reduced. At the same time, the boundary stress was functioned with the crust, the axial force of the side piles was improved. The comparison of measured and calculated results was carried out using the stress reduction ratio, the result shows that the bearing capacity of the subsoil in the crust composite was improved.